SRUKTUR BIAYA PERAWATAN KEBUN KELAPA SAWIT RAKYAT DI KECAMATAN BEUTONG KABUPATEN NAGAN RAYA - Sri Handayani; Aswin Nasution; Amir Amir (Universitas Teuku Umar, 2016)
will give a benefit for farmer. This Research aims to determine the cost of maintenance of folk palm oil plantations in Beutong disrict at Nagan Raya regency based on the group of plantation age. The methods of data analysis was done by descriptive quantitative. The results showed that the maintenance charge for oil palm plantation per hectare immature (TBM) for the plant age 0 years is Rp3.516.200, in age of 1 year is 2.123.700, in age of 2 years is Rp1.923.700 plants, in the age of plant in 3 years is Rp2.323.700. While the maintenance costs of palm oil produce (TM) for age 4-9 years is Rp10.862.800, and age 10-17 years is Rp10.134.600, in age 18-25 years is Rp7.374.000.